Effect of Carvedilol on Thrombocytopenia in Patients with Hepatitis C-Related Cirrhosis - Douna, Samiullah; Zaidi, Yasir Abbas; Umar, Qasim; Safdar, Sohail (Biological and Clinical Sciences Research Journal, 2025)
Thrombocytopenia is a frequent complication in hepatitis C virus (HCV)–related cirrhosis, contributing to heightened bleeding risk and complicating management. Carvedilol, a non-selective β-blocker with additional α₁-adrenergic blocking properties, may alleviate portal hypertension and thereby improve platelet counts. Objective: To evaluate the effect of carvedilol on thrombocytopenia in patients with HCV-related cirrhosis. Methods: This prospective cohort study was conducted in the Department of Gastroenterology at Nishtar Hospital, Multan, Pakistan, from December 2024 to May 2025. Adults aged 20–60 years with PCR-confirmed HCV infection and clinically diagnosed cirrhosis were consecutively enrolled after informed consent. Standard exclusion criteria were applied. Carvedilol was titrated to achieve a 25% reduction from baseline heart rate. Platelet counts and vital signs were recorded at baseline and two weeks after completing the target heart rate, following standardised procedures. The primary outcome was a >15% increase in platelet count from baseline to two weeks (Yes/No). Secondary outcomes included absolute and relative changes in platelet count, and changes in heart rate and blood pressure. Data were analysed using paired t-tests and subgroup comparisons. Results: A total of 176 patients were enrolled (mean age 48.4 ± 9.1 years; 58.0% male). Carvedilol titration achieved the target physiological effects (mean heart rate reduction of −21 bpm; systolic BP reduction of −6 mmHg; diastolic BP reduction of −2 mmHg). Platelet counts increased from 98.2 ± 22.4 to 121.0 ± 26.3 ×10³/mm³ (mean change +22.8 ×10³/mm³; p<0.001). The primary endpoint was met in 68.8% (95% CI 62.0–75.6). No significant effect modification was observed across subgroups defined by age, sex, obesity, Child–Pugh class, variceal grade, diabetes, residence, or disease duration. Conclusion: In patients with HCV-related cirrhosis, carvedilol titrated to a 25% heart-rate reduction was associated with a clinically significant improvement in platelet counts within two weeks in approximately two-thirds of patients, without major hypotensive events. The effect was consistent across major clinical subgroups, supporting its potential role in the management of portal hypertension–associated thrombocytopenia.